John Berryman - American Writers 85 : University of Minnesota Pamphlets on American Writers - Martz, William J. (Book collections on Project MUSE., 1969)
John Berryman - American Writers 85 was first published in 1969. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.